CsATG101 Delays Growth and Accelerates Senescence Response to Low Nitrogen Stress in Arabidopsis thaliana - Huang, Wei; Ma, Danni; Hao, Xulei; Li, Jia; Xia, Li; Zhang, E.; Wang, Pu; Wang, Mingle; Guo, Fei; Wang, Yu; Ni, Dejiang; Zhao, Hua (Frontiers in Plant Science, 2022)
For tea plants, nitrogen (N) is a foundational element and large quantities of N is required during the periods of roundly vigorous growth. However, the fluctuation of N in tea garden could not always meet the dynamic demand of the tea plants. Autophagy, an intracellular degradation process for materials recycling in eukaryotes, plays an important role in nutrient remobilization upon stressful conditions and leaf senescence. Studies have proved that numerous autophagy related genes (ATGs) are involved in N utilization efficiency in Arabidopsis thaliana and other species. Here, we identified an ATG gene, CsATG101, and characterized the potential functions in response to N in A. thaliana. The expression patterns of CsATG101 in four categories of aging gradient leaves among 24 tea cultivars indicated that the autophagy mainly occurred in mature leaves at a relatively high level. Further, the in planta heterologous expression of CsATG101 in A. thaliana was employed to investigate the response of CsATG101 to low N stress. The results illustrated a delayed transition from vegetative to reproductive growth under normal N condition while a premature senescence under N deficient condition in transgenic plants versus the wild type. The expression profiles of twelve AtATGs confirmed the autophagy process especially in mature leaves of transgenic plants. And the relative high expression levels for AtAAP1, AtLHT1, AtGLN1;1 and AtNIA1 in mature leaves illustrated that the mature leaves act as the source leaves in transgenic plants. Altogether, the findings demonstrated that CsATG101 is a candidate gene in improving annual fresh tea leaves yield under both deficient and sufficient N conditions via autophagy process.